ANALISIS YURIDIS EKSEKUSI JAMINAN FIDUSIA UNTUK PERLINDUNGAN PARA PIHAK (STUDI KASUS PUTUSAN PENGADILAN TINGGI PEKANBARU PERKARA No. 36/PDT/2022/PT PBR jo No.242/Pdt.G/2021/PN.Btm) - Sahat Maruli Tua Tampubolon; Lagat Paroha Patar Siadari; Christiani Prasetiasari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Fiduciary Guarantee Law based on Law No. 42 of 1999 concerning Fiduciary Guarantee is the transfer of ownership rights to an object on the basis of trust provided that the object whose ownership rights are transferred remains in the control of the object's owner. Fiduciary guarantee is a form of guarantee institution based on jurisprudence that provides legal protection for the parties. Fiduciary guarantees have main characteristics, including facilitating execution in a simple, fast and low cost way according to the underlying rules. Fiduciary guarantees are evidenced by a fiduciary guarantee certificate which contains instructions